2015
DOI: 10.1017/xps.2015.8
|View full text |Cite
|
Sign up to set email alerts
|

Losing Hurts: The Happiness Impact of Partisan Electoral Loss

Abstract: Partisan identity shapes social, mental, economic, and physical life. Using a novel dataset, we study the consequences of partisan identity by examining the immediate impact of electoral loss and victory on happiness and sadness. Employing a quasi-experimental regression discontinuity model we present two primary findings. First, elections strongly affect the immediate happiness/sadness of partisan losers, but minimally impact partisan winners. This effect is consistent with psychological research on the good-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
53
3
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 45 publications
6
53
3
3
Order By: Relevance
“…The notion of the negativity bias is further reinforced when examining its implications for electoral outcomes. Pierce, Rogers, and Snyder () employ a regression discontinuity design in the context of the 2012 general elections in the United States to examine the emotional well‐being of partisan winner and losers, shortly before and after the elections. They show that partisan losers significantly decrease their reported happiness in the days after the election.…”
Section: Toward a Theory Of Partisan‐biased Citizen Satisfactionmentioning
confidence: 99%
“…The notion of the negativity bias is further reinforced when examining its implications for electoral outcomes. Pierce, Rogers, and Snyder () employ a regression discontinuity design in the context of the 2012 general elections in the United States to examine the emotional well‐being of partisan winner and losers, shortly before and after the elections. They show that partisan losers significantly decrease their reported happiness in the days after the election.…”
Section: Toward a Theory Of Partisan‐biased Citizen Satisfactionmentioning
confidence: 99%
“…Finally, we have no strong predictions regarding the amount of time that the effects of the election results on work engagement and job performance will persist. Prior research on the 2012 US presidential election found that although Republicans were less happy in the week following their candidate’s loss, happiness levels returned to baseline afterwards (Pierce, Rogers, & Snyder, ). Additionally, some scholars have argued that most individuals are resilient and bounce back even from significant trauma (Bonanno, ), suggesting that recovery may be likely.…”
Section: Duration Of the Effect Of Election Results On Work Engagemenmentioning
confidence: 99%
“…For instance, perhaps the unexpected loss of one’s political party or candidate led to feelings of sadness or anger, which then disrupted work engagement. Along these lines, Republicans experienced decreased happiness on the day after Barack Obama’s election win in 2012, and happiness returned to baseline after approximately one week (Pierce et al, ). Thus, there is evidence that presidential elections are associated with changes in emotions over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CivicScience collects over 300,000 survey responses each day via several hundred third-party websites such as newspaper websites, television and radio station websites, and entertainment websites (Pierce, Rogers, and Snyder 2015). CivicScience conducts surveys presented as a series of three questions.…”
Section: Survey Implementationmentioning
confidence: 99%